Science Learning Strategies In Early Childhood Education In The Digital Era: Preparing Early Childhood Kids To Face Global Challenges - Ni Luh Ika Windayani (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
Early Childhood Education (PAUD) plays a crucial role in preparing the young generation to face global challenges in the digital era. This article explores effective science learning strategies in PAUD in the context of digital technology through a literature review from an assortment of sources; both books and scientific journals. Integrating interactive learning applications, videos and animations through an experience-based approach and collaborative projects, children are invited to comprehend science concepts in an excitement and in-depth way. Challenges such as limited access to technology, understanding abstract scientific concepts and the important role of digital literacy are discussed as part of efforts to prepare early childhood education to face an increasingly connected and multifarious world. Collaboration between educators, students and parents is identified as the main key in creating a learning environment that is empowering and relevant for children's futures. It is hoped that with this holistic approach, PAUD can effectively assist children construct a strong foundation in scientific and technological literacy, as well as the skills required to succeed in the digital era.